Correction: Assessing the Feasibility and Acceptability of Smart Speakers in Behavioral Intervention Research With Older Adults: Mixed Methods Study - Kelly Quinn; Sarah Leiser Ransom; Carrie O'Connell; Naoko Muramatsu; David X Marquez; Jessie Chin (Journal of Medical Internet Research)
In “Assessing the Feasibility and Acceptability of Smart Speakers in Behavioral Intervention Research With Older Adults: Mixed Methods Study” (J Med Internet Res 2024;26:e54800) the authors would like to make an addendum to the Acknowledgements: The corrected text should read: This work was supported by the University of Illinois Chicago Center for Clinical and Translational Science; the National Center for Advancing Translational Sciences, National Institutes of Health, through grant UL1TR002003; and the National Institute on Aging of the National Institutes of Health through grant R24AG064191. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health. The funders had no role in the design and conduct of the study; collection, management, analysis, and interpretation of the data; preparation, review, or approval of the manuscript; or decision to submit the manuscript for publication. The authors would like to thank Smit Desai for his contribution to an earlier version of the manuscript. We also would like to thank the following individuals for their assistance with this project: Smit Desai, Jamie Gradishar, Daniel Hlavacek, Faraz Hussain, Caniece Leggett, Fernando Mendez, and Melissa Pierce.